2011
DOI: 10.1089/ten.tea.2009.0721
|View full text |Cite
|
Sign up to set email alerts
|

Scaffold-Based Transplantation of Akt1-Overexpressing Skeletal Myoblasts: Functional Regeneration Is Associated with Angiogenesis and Reduced Infarction Size

Abstract: Myoblast-based therapy can improve cardiac function after infarction and is conventionally performed by direct injection. A scaffold-based transfer could overcome injection-associated problems. In upgrading this approach we transplanted skeletal myoblasts (SkM) overexpressing the prosurvival gene Akt1. SkM were transfected with pcDNA3-huda-Akt1 and seeded on polyurethane scaffolds. These scaffolds were transplanted in rats 2 weeks after myocardial infarction. Hemodynamics were analyzed before therapy and 6 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Previous studies suggested a scaffold-based application of transplanted cells to improve study outcome by avoiding cell loss due to injection, diffusion, or poor engraftment and by preventing injection-induced arrhythmias [18,24]. Unexpectedly, the scaffold-based application of SDF-1 expressing myoblasts to the infarcted heart did not further enhance the positive effects on systolic function observed in group Inj-SDF-1-SkM.…”
Section: Assessment Of Hemodynamic Parametersmentioning
confidence: 86%
“…Previous studies suggested a scaffold-based application of transplanted cells to improve study outcome by avoiding cell loss due to injection, diffusion, or poor engraftment and by preventing injection-induced arrhythmias [18,24]. Unexpectedly, the scaffold-based application of SDF-1 expressing myoblasts to the infarcted heart did not further enhance the positive effects on systolic function observed in group Inj-SDF-1-SkM.…”
Section: Assessment Of Hemodynamic Parametersmentioning
confidence: 86%
“…Interestingly, ECM-initiated survival signaling may be enhanced by direct introduction and overexpression of certain growth factor genes and downstream components of survival signaling pathway, e.g. protein kinase AKT [78]. Advantages, mechanisms and examples of cell transplantations either in aggregates or encapsulated in polymer coating or embedded in biocompatible ECM (hydrogels) have been recently reviewed by Sart and colleagues [79].…”
Section: Pro-death Environment In Damaged Myocardiummentioning
confidence: 99%
“…Although results of initial clinical trials using genetically engineered stem cell therapy are encouraging, many cell survival aspects need to be understood before this approach is fully applied in cardiac repair. A number of pro-survival proteins or angiogenic factors, including connexin Cx43, tumor necrosis factor receptor TNFR, stromal cell-derived factor-1 SDF-1, signaling kinase AKT1, ILK and growth factors HGF, FGF-4 and VEGF-A have been shown to contribute to repopulation of cells when overexpressed in an exact damaged site [78, 175, 209211]. Other data showed that anti-apoptotic BCL-2 transgene expression can efficiently attenuate cardiomyoblast death early after transplantation [212], and that ERBB4 (erb-b2 receptor tyrosine kinase 4) overexpression potentiate MSC survival in the infarcted heart [213].…”
Section: Improving the Cells For Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…16 In some reports, Artelon membrane was precoated with laminin 10 µg/mL at room temperature and cell suspensions containing 5.0 × 10 6 cells were applied to the scaffold. 17 …”
mentioning
confidence: 99%